Effectiveness of Polyhexamethylene biguanide Liquid for Chronic Wound Washing - James, Emmanuel; Massa, Beatrice; Theresa, Mercy (Global Indonesia Health Care (GOICARE), 2024)
Background: Chronic wounds occur due to a failure in the wound healing process and are currently one of the health problems that require proper management. Some types of chronic wounds include venous leg ulcer (VLU), diabetic foot ulcer (DFU). The use of wound washes is one of the factors that play an important role in chronic wound healing. Purpose: Effectiveness of Polyhexamethylene biguanide in cleaning wounds from old dressing residue and reducing bacterial counts. Methods: Quasi experiment without control group to 30 samples using Polyhexamethylene biguanide with BWAT wound assessment instrument (Bates Jensen Wound Assessment Tool), data processing using SPSS program with Wilcoxon test. Results: 17 (40%) were late elderly (56-65 years), 3 (20%) were early elderly (46-55 years), and 10 (20%) were seniors (> 65 years). The bivariate Wilcoxon test shows that Polyhexamethylene biguanide wound cleansing liquid significantly changes mean values before and after wound care. Before wound care, the mean value was 34.65 ± 14.15, and after treatment, it was 7.87 ± 3.16. The mean difference is -5.14 (-12.24 to 2.56) with a 95% confidence interval, and the p value is 0.031. Conclusion: Polyhexamethylene biguanide was shown to be effective as a wound wash to support the healing process of chronic wounds. Suggestions based on the results of this study can be used for efficient chronic wound washing for patients.